UM ESTUDO GEOECONÔMICO DAS LAVANDERIAS INDUSTRIAIS DE JEANS DE CIANORTE (PR) - OBAL, KAROLINE KOLOSINSKI (2017)
The productive especialization in Cianorte grant it the adjectivity of Clothing Capital, making it nationally known for the production of manufactured clothes, especially the jeans. The research works with the hypothesis that the productive restructuring impacted, amongst other productive sectors, the clothing/attirement industry, an important activity in generating employment and income in Cianorte. Being the industrial laundries responsible for the value and visual aggregation of the jeans and constituting a fragmented phase in consequence of the rationalization process of the production. This way, to make our objectives concrete, we analysed the Productive Space Circuit of Jeans and the relationship established with the use of the territory. The theoretical base from the text was build from authors like Santos and Silveira (2006), Moraes (1985), Castillo and Frederico (2010), Antunes (1999), Cardoso (2004), Silva (2012), among others. The data gathering happened through fieldwork, with technical visits and interview aplication to circuit agents; acess to secondary data from sources like the Ministry of Labor and Employment, among others. With the analysis of this data we could come to the formulation that local agents propitiate the development of the sector locally, characterizing a Productive Space Circuit of Jeans nowadays. However, due to be bound to the external logics, the production and employment in Cianorte were strongly affected by the national conjunctures in the last years, registring a significant fall in the manufacturing stage as well as in the washing and local market.